DIGITAL MARKETING AS A TOOL OF PENETRATION IN FOREIGN MARKETS - D. Yampolskaya; V. Starostin; A. Koimur (Вестник университета)
In the article the problem of the appearance of companies on the foreign markets in the current economic conditions has been considered. Upon observation of the data from the international consulting companies an assessment of the state of e-commerce market together with the prospects of its development have been made. The article also summarizes the experience of the world's leading companies in the field of e-commerce. Stemming from this experience some tactical steps to promote e-marketing company are suggested and evaluation of the results of the measures is proposed. It is concluded that the use of e-marketing techniques improves the competitive sustainability of companies in the international markets.